Servitization strategies: shortcomings and opportunities in offering products and services in the agricultural segment - Schaedler, Gustavo Felipe; Cunico, Eliana; Walter, Silvana Anita; Christ, Gabriela Daiana (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – To analyze current and potential servitization strategies, from the perspective of rural producers in the West of the Brazilian state of Parana in relation to its inputs and agricultural equipment. Design/methodology/approach – The study has a qualitative and exploratory approach, based on interviews with rural producers who work in grain production and use products and services related to the supply of inputs for their crops. Findings – Managerially, it was found that producers did not show exclusive loyalty to a certain brand of equipment or agricultural input, but consider the offer of after-sales services and quality technical assistance in the decision. New services demanded by producers were identified and these services may favor purchasing products from the same suppliers. There are gaps that allow exploiting opportunities in terms of servitization, given that not all services that were expected to have been supplied, were supplied by suppliers. Originality/value – This study stands out for its analysis of servitization from the point of view of rural producers in relation to suppliers of agricultural machinery and inputs. It identifies new opportunities in the greater use of technologies, greater transparency and sharing of technical knowledge, improvement of technical assistance and post-sales service at more affordable prices. Keywords – Service; Agribusiness; Production chains; grain production; agricultural inputs.